Parents’ Views on Quality Programmes for Children and the Risks and Benefits They Bring to Preschool Children’s Development and Learning - Sara Seršen; Martina Peštaj; Urška Fekonja (Psychological Topics, 2024)
The aim of this study, which combines a qualitative and a quantitative approach, was to investigate by which standards Slovenian parents of preschool children define a high-quality children’s programme that can be watched on different screens. In addition, we were interested in parents’ views on the risks and benefits that programmes designed for children bring to the child’s early development and learning. The sample included 239 parents of children aged 1 to 6 years. The results show that, on average, children were exposed to screens at the age of two, but individual differences in both the age of first exposure and the frequency of exposure to screen content were substantial. Parents mostly used restrictive mediation to regulate their children’s screen exposure. Overall, parents attached great importance to the different aspects of quality children’s programme and rated aesthetic quality, entertainment and involvement as three very important elements. The standards by which they judged the quality of children’s programme were related to their education and the age of the child. They emphasised the positive effects of children’s programmes on the child’s emotional and language development, imagination and creativity, as well as on the development of social skills and play. On the other hand, the parents were most concerned about violent content, the modelling of inappropriate behaviour and the choice of words in children’s programmes.